The Development of Electronic Pocket Book The Making Oshibana Creation Based Conservation to Train Creative Thinking Student Skill - lisa khoiruz zahro; Ely Rudyatmi (Universitas Negeri Semarang, 2023)
The integration of conservation-based education in online learning through paperless. Students are also assigned to make oshibana creations that apply eco-green principles to train creative thinking skills. Student’s creative thinking skills during Covid-19 decreased. This is caused by a reduction in learning hours and limited learning media. So it is necessary to develop an electronic pocket book for making oshibana creations based on conservation. The purpose of this study was to analyze the feasibility, practicality, and effectiveness of electronic pocket book for making oshibana based conservation creations to train students creative thinking skills. This research is development research using the 4D model (define, design, development, disseminate). The feasibility of electronic pocket books is determined based on the media and material expert validation sheets. The practicality of the electronic pocket book was determined based on the teacher's and students' response questionnaires in class X APHP SMK 3 Kudus. The effectiveness of the electronic pocket book is determined based on the product assessment sheet and the student response questionnaire sheet on the use of the electronic pocket book. The results of the media expert's assessment was 95.83% (very feasible) and the material expert's assessment was 96.66% (very feasible). Teachers argue practical electronic pocket book. 20.5% of students think it is very practical, 73.5% practical and 5.8% quite practical. The number of students is very creative and creative 76.46%. 76% of students think very good, 21% good, and 3% less good about the use of electronic pocket books. This means that the electronic pocket book for making based conservation creations that has been developed is very feasible, practical, and effective to train students creative thinking skills